(3JMaI GdXQaGA aj LeY eGaj GdcdGYj ef GdQSGFd GdfHhjI hGdUMGHI GdNdaGAs - (3eMeO Hf CMeO Hf GdMSf GdjMeOj GdaMUjs; (3eMeO Hf GdMSf Hf CMeO GdjMeOj,J (B1130 (3g` ? s
(3ChdgG (B:s
(3CeG HYO aEfi deG WGdYJ cJGH GdEcJaGA MOKJfj faSj Cf CdNU ef GdcJGH GdePchQ QSGFdg Udi Gddg Yjg hSde hQSGFd CUMGHg ef HYOg GdNdaGA GdQGTOjf hCeQGA LjhTge s
(3BNQgG (B:s
(3hgPG eGJjSQ eY GdHGd, cKQI GdCTZGd s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B322s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B98 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs